Air Rebusan Seledri Menurunkan Tekanan Darah - Wiwik Afridah (Universitas Nahdlatul Ulama Surabaya, 2015)
The increasing elderly population will lead to problems such as health problems, one of which is hypertension. The purpose of this study was to determine the effect of celery stew on blood pressure in elderly people with hypertension Hulaan Village District Menganti Gresik regency.